Effects of a Portuguese social–emotional learning program on the competencies of elementary school students - Coelho, Vera; Peixoto, Carla; Azevedo, Helena; Machado, Francisco; Soares, Mónica; Espain, Andreia (Frontiers in Psychology, 2023)
Introduction It is widely recognized that socio-emotional learning (SEL) interventions can contribute to supporting students’ positive development of socio-emotional skills (SES) and positive relationships with peers and teachers. Thus, interest in promoting students’ SES through universal evidence-based programs is spreading around the world, including in Portuguese schools. Methods This quasi-experimental study examines the efficacy of a SEL classroom-based program, infused into the curriculum, on students’ communication, self-regulation, and classroom peer relationships. Participants included 208 third- to fourth-grade students from three Portuguese public elementary schools: 143 in the intervention group (54.5% boys; Mage = 8.72; SD = 0.61); 65 in the comparison group (52.3% boys; Mage = 8.66; SD = 0.59). Measures included: Study on Social and Emotional Skills, parent, child, and teacher versions; and Classroom Peer Context Questionnaire, completed by students. The study followed a pre- and post-test design, with a 16-week intervention. Results For the overall participants, results show a positive effect of the program on students’ assertiveness (family report), peer conflict and peer cooperation. Effects were analyzed separately by school grade. A statistically significant positive effect of the program on third-grade students’ assertiveness and sociability was found. For fourth-grade students, a positive effect was found on - emotional control). classroom conflicts, isolation, cooperation and cohesion behaviors. Discussion These positive effects support the expansion of universal interventions when aiming at strengthening SEL in Portuguese school settings, underlining the relevance of embedding SEL into the curricula and daily practices at schools.